Perceived psychosocial impacts of legalized same-sex marriage: A scoping review of sexual minority adults’ experiences - Drabble, Laurie A. (PLoS One, 2021)
A growing body of literature provides important insights into the meaning and impact of the right to marry a same-sex partner among sexual minority people. We conducted a scoping review to 1) identify and describe the psychosocial impacts of equal marriage rights among sexual minority adults, and 2) explore sexual minority women (SMW) perceptions of equal marriage rights and whether psychosocial impacts differ by sex. Using Arksey and O’Malley’s framework we reviewed peer-reviewed English-language publications from 2000 through 2019. We searched six databases (PubMed, PsycINFO, CINAHL, Web of Science, JSTOR, and Sociological Abstracts) to identify English language, peer-reviewed journal articles reporting findings from empirical studies with an explicit focus on the experiences and perceived impact of equal marriage rights among sexual minority adults. We found 59 studies that met our inclusion criteria. Studies identified positive psychosocial impacts of same-sex marriage (e.g., increased social acceptance, reduced stigma) across individual, interpersonal (dyad, family), community (sexual minority), and broader societal levels. Studies also found that, despite equal marriage rights, sexual minority stigma persists across these levels. Only a few studies examined differences by sex, and findings were mixed. Research to date has several limitations; for example, it disproportionately represents samples from the U.S. and White populations, and rarely examines differences by sexual or gender identity or other demographic characteristics. There is a need for additional research on the impact of equal marriage rights and same-sex marriage on the health and well-being of diverse sexual minorities across the globe.